Asphalt sizing material, preparation method thereof and high-flame-retardant exposed tire-free asphalt coiled material

By using SIS and SBR in asphalt materials, combining decabromodiphenylethane and aluminum foil glass fiber composite flame retardant film layer, traditional asphalt coils are easily hardened, brittle and flammable under low temperature conditions. The problem of this problem achieves efficient flame retardant and peeling performance, meeting modern use requirements.

CN119144278APending Publication Date: 2024-12-17福建省三棵树新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411241508.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional asphalt waterproof coils are prone to hardening and brittle under low temperature conditions, have low peeling strength, and are flammable, which cannot effectively prevent the spread of fire and cannot meet the existing use requirements.

Method used

Styrene-isoprene-styrene block copolymer (SIS) is used as macromolecular framework structure, combined with styrene butadiene rubber (SBR) and decabromodiphenylethane as flame retardant components to optimize the low temperature flexibility of the rubber and cohesive force, and achieves high-efficiency flame retardant effect through aluminum foil glass fiber composite flame retardant film layer.

Benefits of technology

It improves the low-temperature flexibility and peel strength of asphalt rubber, achieves efficient flame retardant performance, and meets the construction application performance and safety performance of asphalt waterproof coils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144278A_ABST
    Figure CN119144278A_ABST
Patent Text Reader

Abstract

The asphalt sizing material is prepared from the following components in parts by weight: 45 to 46 parts of 70 # asphalt, 9 to 10 parts of rubber oil, 4 to 5 parts of aromatic hydrocarbon oil, 6 to 7 parts of styrene-isoprene-styrene block copolymer, 7 to 8 parts of butadiene styrene rubber powder, 1 to 2 parts of styrene-butadiene-styrene block copolymer, 4 to 5 parts of desulfurized tire rubber powder, 8 to 10 parts of decabromodiphenyl ethane and 10 to 20 parts of silica powder. According to the present invention, the styrene-isoprene-styrene block copolymer (SIS) is adopted as the main material, and the styrene butadiene rubber (SBR) is adopted as the auxiliary material, such that on one hand, the low temperature flexibility of the rubber material can be substantially improved, and the hardening, the embrittlement, the cracking and other conditions of the prepared waterproof coiled material at the low temperature can be reduced to a certain extent; on the other hand, compared with SBS, SIS is longer in molecular chain segment, better in flexibility, larger in structural space, convenient for nesting and filling of small molecular substances, and capable of exerting the viscosity of a rubber state to a greater extent, optimizing cohesion and improving the aluminum plate peel strength of the waterproof roll by matching with active unsaturated double bonds of SBR to generate chemical connection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, and in particular to an asphalt rubber material and a preparation method thereof, and a highly flame-retardant exposed tireless asphalt coiled material. Background Art

[0002] Waterproof membranes are used in buildings to prevent water leakage and penetration. Among them, the most widely used ones in the market are asphalt waterproof membranes. However, for this type of membrane, the asphalt used as the adhesive is not ideal in terms of low-temperature flexibility and cohesion, which causes the membrane to become hard and brittle under low temperature conditions, and may even crack in severe cases. When the cohesion is insufficient, the peel strength decreases and it is easy to separate from the base surface, which is not conducive to the waterproof effect.

[0003] In addition, conventional asphalt waterproofing membranes are flammable materials. When encountering a fire, they cannot prevent the spread of fire and have low safety performance. During the use of such waterproofing membranes, inorganic flame retardants such as hydroxides are usually added to improve the flame retardancy of the membranes. However, if the amount of inorganic flame retardants added is small, the ideal flame retardant effect cannot be achieved (the general amount added is higher than 20%); if the amount added is large, on the one hand, since asphalt is a flammable substance, even if a large amount of inorganic flame retardants are added, it is difficult to turn it from a flammable material into a non-flammable material, and a good flame retardant effect cannot be achieved. On the other hand, the low temperature resistance and peel strength of the membrane will be greatly reduced.

[0004] Therefore, traditional asphalt waterproof membranes can no longer meet existing usage requirements, and there is an urgent need to develop a new type of asphalt waterproof membrane with excellent low temperature resistance, high peel strength and good flame retardancy. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an asphalt rubber material and a preparation method thereof, and a highly flame-retardant exposed tireless asphalt coil.

[0006] The technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides an asphalt rubber material, comprising, by weight:

[0008] 45-46 parts of 70# asphalt, 9-10 parts of rubber oil, 4-5 parts of aromatic oil, 6-7 parts of styrene-isoprene-styrene block copolymer, 7-8 parts of styrene-butadiene rubber powder, 1-2 parts of styrene-butadiene-styrene block copolymer, 4-5 parts of desulfurized tire rubber powder, 8-10 parts of decabromodiphenyl ethane, and 10-20 parts of silica powder.

[0009] The present invention proposes an asphalt adhesive. Different from the traditional self-adhesive waterproof membrane adhesive which uses styrene-butadiene-styrene block copolymer (SBS) as the macromolecular framework structure, the present invention selects a compounding method of styrene-isoprene-styrene block copolymer (SIS) as the main component and styrene-butadiene rubber (SBR) as the auxiliary component. On the one hand, the low-temperature flexibility of the adhesive can be greatly improved, and to a certain extent, the hardening, brittleness and cracking of the waterproof membrane prepared at low temperatures can be alleviated; on the other hand, compared with SBS, SIS has longer molecular chains, better flexibility and larger structural space, which is convenient for nesting and filling of small molecular substances. Combined with the active unsaturated double bonds of SBR to produce chemical connections, the viscosity of the rubber state can be exerted to a greater extent, the cohesive force can be optimized, and the aluminum plate peeling strength of the waterproof membrane can be improved. At the same time, the present invention introduces decabromodiphenylethane as a flame retardant component, and its addition amount can be controlled below 10%. During the thermal decomposition process of the asphalt rubber, decabromodiphenylethane can release HBr that consumes the product of the polymer combustion chain reaction. On the one hand, HBr can react with chain reaction active substances such as ·OH and ·O· in the flame, thereby reducing the concentration of free radicals and ultimately slowing down or terminating the chain reaction in the combustion process; on the other hand, HBr itself is non-flammable and has a large density. It covers the surface of the asphalt and can isolate the combustible gas on its surface, thereby achieving a flame retardant effect.

[0010] Preferably, the softening point of the 70# asphalt is 44-54°C, and the needle penetration is 60-80 / 0.1mm.

[0011] Preferably, the rubber oil has a viscosity of 100-1000 mPa·s and a pour point of -20°C.

[0012] Preferably, the viscosity of the aromatic oil is 3000-12000 mPa·s.

[0013] Preferably, the molecular weights of the styrene-isoprene-styrene block copolymer and the styrene-butadiene-styrene block copolymer are both not higher than 300,000.

[0014] Preferably, the particle size of the desulfurized tire rubber powder is 80 mesh.

[0015] Preferably, the silicon micropowder has a bulk density of 60-80 g / 100 ml, an oil absorption value of 20-30 ml / 100 g, and a particle size of 1000-1500 mesh.

[0016] In a second aspect, the present invention provides a method for preparing an asphalt rubber as described in any one of the above technical solutions, comprising the following steps:

[0017] S1. Mix 70# asphalt, rubber oil and aromatic oil, heat to 140℃ for dehydration for 30min, and stir synchronously at a frequency of 10-20Hz;

[0018] S2. After dehydration, add styrene-butadiene rubber powder, control the temperature to 140-155°C, and stir at a frequency of 30-35Hz for 60min;

[0019] S3, raising the temperature to 180°C, adding styrene-isoprene-styrene block copolymer and styrene-butadiene-styrene block copolymer, stirring at a frequency of 20 Hz for 60 min, and then grinding with a colloid mill for 120 min, with a colloid mill gap of 0.3 mm;

[0020] S4, keep the temperature constant, add desulfurized tire rubber powder and decabromodiphenylethane, stir at a frequency of 30 Hz for 120 minutes, and then grind with a colloid mill for 120 minutes, with a gap of 0.3 mm;

[0021] S5. Keep the temperature unchanged, add silicon micropowder at a feeding rate of 1t / h, and stir at a frequency of 30-35Hz for 120min.

[0022] In the third aspect, the present invention provides a highly flame retardant exposed tubeless asphalt roll material, which includes, from top to bottom, an aluminum foil and glass fiber composite flame retardant film layer, a first asphalt rubber layer, a PE polymer film layer, a second asphalt rubber layer and a PET isolation film layer, wherein the first asphalt rubber layer and the second asphalt rubber layer are both formed by the asphalt rubber described in any of the above technical solutions.

[0023] Preferably, the thickness of the second asphalt rubber layer is 0.8-1.0 mm;

[0024] The thickness of the highly flame-retardant exposed tubeless asphalt coil is 1.5 mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic structural diagram of the highly flame-retardant exposed tubeless asphalt roll material according to Example 1 of the present invention.

[0026] [Description of Reference Numerals]

[0027] 1. Aluminum foil and glass fiber composite flame retardant film layer; 2. First asphalt rubber layer; 3. PE polymer film layer; 4. Second asphalt rubber layer; 5. PET isolation film layer. DETAILED DESCRIPTION

[0028] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0029] In one aspect, the present invention provides an asphalt rubber material, comprising, by weight:

[0030] 45-46 parts of 70# asphalt, 9-10 parts of rubber oil, 4-5 parts of aromatic oil, 6-7 parts of styrene-isoprene-styrene block copolymer, 7-8 parts of styrene-butadiene rubber powder, 1-2 parts of styrene-butadiene-styrene block copolymer, 4-5 parts of desulfurized tire rubber powder, 8-10 parts of decabromodiphenyl ethane, and 10-20 parts of silica powder.

[0031] In the present invention, SIS is used in asphalt rubber to replace part of SBS, and is compounded with SBR as the main modifying component. Under the specific ratio of the three, the asphalt rubber has better low-temperature flexibility and peeling strength; by combining with rubber oil, aromatic oil and desulfurized tire rubber powder, the low-temperature flexibility and peeling performance of the asphalt rubber can be further optimized, thereby ensuring the construction application performance of the prepared waterproof membrane in a low-temperature environment.

[0032] In a preferred embodiment of the present invention, the softening point of the 70# asphalt is 44-54°C, and the needle penetration is 60-80 / 0.1mm. In the present invention, the formulation system of the present invention belongs to a typical self-adhesive system, which does not require high temperature performance of the asphalt rubber, but focuses on low temperature performance and peeling performance. Compared with the 70# asphalt used in the present invention, the 10# asphalt has a higher softening point and greater hardness due to the large amount of asphaltene, but its touch adhesion is poor. If it is used in the self-adhesive system of the present invention, it will seriously affect the peeling performance of the coiled material, and as time goes by, the coiled material will become harder and harder, and the viscosity will seriously decrease, so that the peeling performance of the aluminum plate cannot meet the requirements.

[0033] In a preferred embodiment of the present invention, the viscosity of the rubber oil is 100-1000 mPa·s and the pour point is -20°C.

[0034] In a preferred embodiment of the present invention, the viscosity of the aromatic oil is 3000-12000 mPa·s. In the present invention, a high-viscosity aromatic oil is introduced, which belongs to liquid oil and can still flow at 5°C. The present invention can increase the melting rate of the modified components SIS / SBR / SBS on the one hand, and better balance the cohesion and optimize the low-temperature flexibility and peeling performance of the asphalt rubber on the other hand by matching the high-viscosity aromatic oil in a specific ratio with the rubber oil of lower viscosity. Compared with C9 petroleum resin, since C9 petroleum resin is a solid resin with a softening point of 80-140°C, it is relatively brittle and has poor low-temperature performance. If it is used in the self-adhesive system of the present invention, although it can increase the softening point of asphalt, it will lead to an increase in the overall hardness and a large cohesion, which has a significant negative impact on the low-temperature and peeling performance of the coiled material.

[0035] In a preferred embodiment of the present invention, the molecular weights of the styrene-isoprene-styrene block copolymer and the styrene-butadiene-styrene block copolymer are both not higher than 300,000. In the present invention, by limiting the relative molecular weights of SIS and SBS, it is beneficial to optimize the low temperature flexibility and peeling performance of the asphalt rubber.

[0036] In a preferred embodiment of the present invention, the particle size of the desulfurized tire rubber powder is 80 mesh. In the present invention, selecting 80 mesh desulfurized tire rubber powder and controlling its ratio with SBR is beneficial to improving the viscosity of the asphalt rubber, thereby improving the stripping performance of the coiled material.

[0037] In a preferred embodiment of the present invention, the bulk density of the silicon micropowder is 60-80g / 100ml, the oil absorption value is 20-30ml / 100g, and the particle size is 1000-1500 mesh. In the present invention, the traditional stone powder filler with a bulk density of 90-100g / 100ml is abandoned, and the silicon micropowder with a bulk density of 60-80g / 100m is selected as the filler, so as to further reduce the weight of the coiled material and reduce the building load-bearing in subsequent projects.

[0038] Another aspect of the present invention provides a method for preparing an asphalt rubber as described in any one of the above technical solutions, comprising the following steps:

[0039] S1. Mix 70# asphalt, rubber oil and aromatic oil, heat to 140℃ for dehydration for 30min, and stir synchronously at a frequency of 10-20Hz;

[0040] S2. After dehydration, add styrene-butadiene rubber powder, control the temperature to 140-155°C, and stir at a frequency of 30-35Hz for 60min;

[0041] S3, raising the temperature to 180°C, adding styrene-isoprene-styrene block copolymer and styrene-butadiene-styrene block copolymer, stirring at a frequency of 20 Hz for 60 min, and then grinding with a colloid mill for 120 min, with a colloid mill gap of 0.3 mm;

[0042] S4, keep the temperature constant, add desulfurized tire rubber powder and decabromodiphenylethane, stir at a frequency of 30 Hz for 120 minutes, and then grind with a colloid mill for 120 minutes, with a gap of 0.3 mm;

[0043] S5. Keep the temperature unchanged, add silicon micropowder at a feeding rate of 1t / h, and stir at a frequency of 30-35Hz for 120min.

[0044] In the present invention, the process conditions need to be strictly controlled during the preparation of asphalt rubber, wherein SBR powder must be fed at a low temperature of 140-155°C and the stirring frequency must not be lower than 30Hz. This is attributed to the fact that SBR contains a large number of unsaturated double bonds. When the temperature exceeds 155°C, its reaction activity is greatly improved and it is easy to self-aggregate. In order to further improve its dispersion uniformity, it can be ground and dispersed. For the added silicon micropowder, since its particle size is several 1000-1500 mesh, which is much higher than the traditional stone powder filler of 200 mesh, its feeding speed and stirring frequency need to be controlled.

[0045] On the other hand, the present invention provides a highly flame-retardant exposed tubeless asphalt coil, which includes, from top to bottom, an aluminum foil and glass fiber composite flame-retardant film layer 1, a first asphalt rubber layer 2, a PE polymer film layer 3, a second asphalt rubber layer 4 and a PET isolation film layer 5, wherein the first asphalt rubber layer 2 and the second asphalt rubber layer 4 are both formed by the asphalt rubber described in any of the above technical solutions.

[0046] In the present invention, a dual flame retardant design is adopted, by introducing decabromodiphenylethane into the inner layer asphalt rubber formula, and using aluminum foil glass fiber composite flame retardant film for the outer layer, to achieve the dual functions of being exposed and highly effective flame retardant. When encountering fire, on the one hand, the inner layer decabromodiphenylethane produces HBr, which can capture free radicals and prevent free radical chain reactions, and can also block oxygen and inhibit asphalt combustion; on the other hand, the aluminum in the outer layer aluminum foil glass fiber composite flame retardant film burns in the air to generate high melting point aluminum oxide, which is deposited on the surface of the coil to form a certain protective layer to prevent the combustion chain reaction. The two work together to play a highly effective flame retardant role. Compared with adding aluminum hydroxide and decabromodiphenylethane directly to the asphalt rubber, this design has the following advantages: First, since asphalt itself is a combustible material, it is difficult to turn it from a combustible material into a non-combustible material even if a large amount of aluminum hydroxide is added. It can only slow down the combustion speed, reduce the combustion range, or make its dripping self-extinguish within a certain period of time. Therefore, directly adding the above two substances to the asphalt cannot achieve a good flame retardant effect, and there is still a great risk of igniting other combustibles. The present invention uses an aluminum foil glass fiber composite flame retardant film as the outer layer, which can play a good isolation role when the flame reaches the surface of the coil. At the same time, the aluminum oxide produced covers the surface of the asphalt coil, which plays a non-combustible role to a certain extent. Second, aluminum hydroxide itself has a strong hydrophilicity and poor compatibility with asphalt-like substances. Adding a higher proportion will affect the continuity of the asphalt rubber, and further affect its viscosity and aluminum plate peeling index.

[0047] In addition, although the present invention does not impose any special restrictions on the preparation method of the highly flame-retardant exposed tireless asphalt coil, it should be noted that since the middle layer is compounded with PE polymer film and asphalt rubber, in order to ensure the mechanical properties of the coil, the temperature of the asphalt rubber needs to be lowered to 145-165°C during film coating to reduce the deformation of the PE polymer film due to heat. In addition, since the elongation of the PE polymer film is relatively high, the molding process adopts double-roll extrusion molding, which is pulled forward by multiple transmission rollers, which will produce corresponding stress stretching. In order to reduce the shrinkage problem during the coil construction process, it is necessary to control the production vehicle speed, reasonably set the production line tension, and control the production line operation speed at 20-40m / min.

[0048] In a preferred embodiment of the present invention, the thickness of the second asphalt rubber layer 4 is 0.8-1.0 mm;

[0049] The thickness of the highly flame-retardant exposed tubeless asphalt coil is 1.5 mm.

[0050] In the present invention, conventional self-adhesive rolls are all made of a single-layer rubber structure, and the rubber thickness can reach 1.5 mm. However, the present invention adopts a double-sided sandwich rubber structure design divided by a PE polymer film, so the effective bonding thickness between the roll and the aluminum plate becomes thinner, which increases the difficulty of meeting the aluminum plate peeling performance standard of the roll. However, since the viscosity of the asphalt rubber of the present invention is better than that of the conventional rubber, it is only necessary to control the cutting thickness of the second asphalt rubber layer 4 to 0.8-1.0 mm to ensure that the aluminum plate peeling index of the obtained highly flame-retardant and exposed tireless asphalt roll is qualified.

[0051] Example 1

[0052] An asphalt rubber material comprising, by weight:

[0053] 45 parts of 70# asphalt, 9 parts of rubber oil, 4 parts of aromatic oil, 6 parts of styrene-isoprene-styrene block copolymer, 7 parts of styrene-butadiene rubber powder, 2 parts of styrene-butadiene-styrene block copolymer, 4 parts of desulfurized tire rubber powder, 8 parts of decabromodiphenyl ethane, and 15 parts of silica powder.

[0054] The softening point of the 70# asphalt is 52°C and the needle penetration is 63.5 / 0.1mm.

[0055] The viscosity of the rubber oil is 253 mPa·s and the pour point is -20°C.

[0056] The viscosity of the aromatic oil is 7800 mPa·s.

[0057] The molecular weights of the styrene-isoprene-styrene block copolymer and the styrene-butadiene-styrene block copolymer are both not higher than 300,000.

[0058] The particle size of the desulfurized tire rubber powder is 80 meshes.

[0059] The silicon micropowder has a bulk density of 75 g / 100 ml, an oil absorption value of 22.5 ml / 100 g, and a particle size of 1250 meshes.

[0060] It is prepared by the following method, comprising the following steps:

[0061] S1. Mix 70# asphalt, rubber oil and aromatic oil, heat to 140℃ for dehydration for 30min, and stir synchronously at a frequency of 15Hz;

[0062] S2. After dehydration, add styrene-butadiene rubber powder, control the temperature at 150°C, and stir at a frequency of 35 Hz for 60 minutes;

[0063] S3, raising the temperature to 180°C, adding styrene-isoprene-styrene block copolymer and styrene-butadiene-styrene block copolymer, stirring at a frequency of 20 Hz for 60 min, and then grinding with a colloid mill for 120 min, with a colloid mill gap of 0.3 mm;

[0064] S4, keep the temperature constant, add desulfurized tire rubber powder and decabromodiphenylethane, stir at a frequency of 30 Hz for 120 minutes, and then grind with a colloid mill for 120 minutes, with a gap of 0.3 mm;

[0065] S5. Keep the temperature unchanged, add silica powder, feed at a rate of 1 t / h, and stir at a frequency of 35 Hz for 120 min to obtain asphalt rubber.

[0066] The asphalt rubber compound prepared by the above method is used to prepare a highly flame retardant and exposed tireless asphalt coiled material. The specific method is: wait for the asphalt rubber compound to cool to 160°C, and then coat the asphalt rubber compound on a molding line to obtain a highly flame retardant and exposed tireless asphalt coiled material. Figure 1 As shown, the highly flame retardant exposed tubeless asphalt coil includes, from top to bottom, an aluminum foil glass fiber composite flame retardant film layer 1, a first asphalt rubber layer 2, a PE polymer film layer 3, a second asphalt rubber layer 4 and a PET isolation film layer 5, wherein the first asphalt rubber layer 2 and the second asphalt rubber layer 4 are both formed by the asphalt rubber prepared by the above method.

[0067] Wherein, the thickness of the second asphalt rubber layer 4 is 0.9 mm;

[0068] The thickness of the highly flame-retardant exposed tubeless asphalt coil is 1.5 mm.

[0069] Example 2

[0070] The difference between this embodiment and embodiment 1 is that the amounts of the components are different, see Table 1 for details. The remaining steps remain unchanged.

[0071] Comparative Example 1-2

[0072] The difference between this comparative example and Example 1 is that the amounts of SIS and SBS are different, see Table 1 for details. The other steps remain unchanged.

[0073] Comparative Examples 3-5

[0074] The difference between this comparative example and Example 1 is that the amounts of SBR powder and desulfurized tire rubber powder are different, see Table 1 for details. The remaining steps remain unchanged.

[0075] Comparative Examples 6-10

[0076] The difference between this comparative example and Example 1 is that the amounts of rubber oil and aromatic oil used are different, wherein the comparative example 10 uses 100 parts of silicon micropowder, as shown in Table 1. The remaining steps remain unchanged.

[0077] Comparative Examples 11-12

[0078] The difference between this comparative example and Example 1 is that the amounts of decabromodiphenylethane and silicon powder used are different, see Table 1 for details. The other steps remain unchanged.

[0079] Table 1 Raw material ratios of each embodiment and comparative example

[0080]

[0081]

[0082] The waterproof membranes prepared in Examples 1-2 and Comparative Examples 1-12 were subjected to performance tests, and the results are recorded in Tables 2 and 3.

[0083] Table 2 Performance test results of waterproof membranes prepared in various embodiments and comparative examples

[0084]

[0085] Table 3 Performance test results of highly flame-retardant exposed tireless asphalt membrane prepared in Example 1

[0086]

[0087] It can be seen from the results of Table 2 and Table 3 that the highly flame-retardant exposed tireless asphalt coiled material prepared in the embodiment of the present invention has excellent low temperature performance, peel strength, flame retardancy, aging resistance, waterproof performance and other properties, and can well meet the construction application performance of self-adhesive asphalt waterproof coiled material. Comparing Example 1 with Comparative Examples 1-2, it can be seen that when the amount of SBR remains unchanged, if SBS is used as the main modifier to construct the macromolecular framework, when its proportion reaches 3% (Comparative Example 1), the cohesion of the coiled material is too large, and when it is bonded to the aluminum plate, the internal bonding force of the asphalt rubber is much greater than the bonding force between the asphalt rubber and the aluminum plate, the coiled material is too hard, and the test data of the aluminum plate is unqualified; when SIS is used as the main modifier and SBS is not added (Comparative Example 2), the cohesion of the coiled material is too small, and the aluminum plate data surplus is small. Under the preferred SIS and SBS ratio of the present invention, the cohesion of the coiled material is reasonable and the peeling strength of the aluminum plate is good. By comparing Example 1 with Comparative Examples 3-5, it can be seen that when the total amount of SBR powder and desulfurized tire rubber powder remains unchanged, when the amount of desulfurized tire rubber powder is less than 4%, the viscosity of the asphalt rubber is thin, and the coil cannot meet the requirements of high temperature resistance; when the amount of SBR powder is less than 7%, the viscosity of the asphalt rubber is low, and the aluminum plate peeling strength of the coil cannot meet the standard. By comparing Example 1 with Comparative Examples 6-10, it can be seen that the optimal ratio of rubber oil to aromatic oil is 9 parts of rubber oil + 4 parts of aromatic oil. When the rubber oil ratio is less than 9%, it directly affects the low temperature performance of the coil, causing it to become brittle; when the rubber oil ratio reaches 13%, the viscosity of the asphalt rubber is thin, soft, and the surface is oily, and the high temperature resistance and aluminum plate peeling strength of the coil are greatly reduced; when the aromatic oil ratio is less than 4%, the viscosity of the asphalt rubber decreases, and the aluminum plate peeling performance of the coil cannot meet the requirements. Comparing Example 1 with Comparative Examples 11-12, under the dual flame retardant system, if the addition amount of decabromodiphenylethane is less than 8%, the flame retardant effect of B1 level cannot be achieved.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An asphalt rubber compound, characterized in that: Including by weight: 45-46 parts of 70# asphalt, 9-10 parts of rubber oil, 4-5 parts of aromatic oil, 6-7 parts of styrene-isoprene-styrene block copolymer, 7-8 parts of styrene-butadiene rubber powder, 1-2 parts of styrene-butadiene-styrene block copolymer, 4-5 parts of desulfurized tire rubber powder, 8-10 parts of decabromodiphenyl ethane, and 10-20 parts of silica powder.

2. The asphalt rubber material according to claim 1, characterized in that: The softening point of the 70# asphalt is 44-54°C, and the needle penetration is 60-80 / 0.1mm.

3. The asphalt rubber material according to claim 1, characterized in that: The rubber oil has a viscosity of 100-1000 mPa·s and a pour point of -20°C.

4. The asphalt rubber material according to claim 1, characterized in that: The viscosity of the aromatic oil is 3000-12000 mPa·s.

5. The asphalt rubber material according to claim 1, characterized in that: The molecular weights of the styrene-isoprene-styrene block copolymer and the styrene-butadiene-styrene block copolymer are both not higher than 300,000.

6. The asphalt rubber material according to claim 1, characterized in that: The particle size of the desulfurized tire rubber powder is 80 meshes.

7. The asphalt rubber material according to claim 1, characterized in that: The silicon micropowder has a bulk density of 60-80 g / 100 ml, an oil absorption value of 20-30 ml / 100 g, and a particle size of 1000-1500 meshes.

8. A method for preparing an asphalt rubber compound according to any one of claims 1 to 7, comprising the following steps: S1. Mix 70# asphalt, rubber oil and aromatic oil, heat to 140℃ for dehydration for 30min, and stir synchronously at a frequency of 10-20Hz; S2. After dehydration, add styrene-butadiene rubber powder, control the temperature to 140-155°C, and stir at a frequency of 30-35Hz for 60min; S3, raising the temperature to 180°C, adding styrene-isoprene-styrene block copolymer and styrene-butadiene-styrene block copolymer, stirring at a frequency of 20 Hz for 60 min, and then grinding with a colloid mill for 120 min, with a colloid mill gap of 0.3 mm; S4, keep the temperature constant, add desulfurized tire rubber powder and decabromodiphenylethane, stir at a frequency of 30 Hz for 120 minutes, and then grind with a colloid mill for 120 minutes, with a gap of 0.3 mm; S5. Keep the temperature unchanged, add silicon micropowder at a feeding rate of 1t / h, and stir at a frequency of 30-35Hz for 120min.

9. A highly flame-retardant exposed tireless asphalt coil, characterized in that: From top to bottom, it includes an aluminum foil glass fiber composite flame retardant film layer, a first asphalt rubber layer, a PE polymer film layer, a second asphalt rubber layer and a PET isolation film layer, wherein the first asphalt rubber layer and the second asphalt rubber layer are both formed by the asphalt rubber described in any one of claims 1-7.

10. The highly flame-retardant exposed tubeless asphalt coiled material according to claim 9, characterized in that: The thickness of the second asphalt rubber layer is 0.8-1.0 mm; The thickness of the highly flame-retardant exposed tubeless asphalt coil is 1.5 mm.